Outbound tourism from Soviet Belarus as a new battle line in the Cold War during the Khrushchev’s thaw - Huzhalouski, Alexander A. (Journal of the Belarusian State University. International Relations, 2023)
This article explores the use of outbound tourism during the Khrushchev’s thaw as a Cold War propaganda tactic for publicising the Soviet project abroad. Despite a threefold rise in tourist numbers, the primary goal of outbound tourism during the thaw years was the same as in the preceding years. The Soviet tourist was expected to build the USSR’s international image and standing with their appearance, words, and actions, and their mere presence was supposed to demonstrate the freedom of movement they enjoyed at home. The Belarusian Society for Cultural Relations with Foreign Countries, the Minsk branch of the agency “Intourist”, the Central Committee of the CPSU’s commission for trips abroad, and the tourist and excursion division of the Belarusian Republican Council of Trade Unions all handled the organisational and technical aspects of outbound tourism. The international youth tourism bureau “Sputnik” created in 1958, was also vested with a similar function. The study reconstructs the institutional and organisational-legal landscape, the volumes and geographic scope, and also the forms and features of Soviet outbound international tourism in 1955–1968, using archive materials, published sources, and post-Soviet and Western historiography. By employing a non-institutional, anthropological approach, the author was able to take into account not only the actions of the bodies that organised Soviet citizens’ travel abroad but also the political and ideological significance of these journeys, as well as the hidden behaviours of Soviet tourists during the Cold War.